The Poor in Court: The Legal Services Program and Supreme Court Decision Making - Susan E. Lawrence (Princeton University Press, 2014)
LINCOLN once remarked, "God must have loved poor people, he made so many of them." Not surprisingly, in a legal system where the ability to retain and compensate an attorney is, effectively, a prerequisite to participation in judicial decision making, the bar and the courts have been somewhat less enamored of the indigent. Throughout most of our history, few of the poor have been able to turn to the courts for redress of their grievances and participate in the judicial development of law and policy. In the late 1960s, the Supreme Court suddenly began to give substantial attention to poverty issues outside the criminal justice process, using the due process and equal protection clauses to supervise the state's interaction with the less fortunate among us. The Legal Services Program (LSP), created in 1965 as part of the Office of Economic Opportunity, played a seminal role in precipitating this change in the Court's agenda and doctrinal development. By providing counsel to the poor and litigating well over a million civil cases, including 164 that percolated up the appellate ladder to the Supreme Court between 1966 and 1974, the LSP changed the parameters of access to one of our major governing institutions. The poor, represented by Legal Services attorneys, provided the Supreme Court with a new set of opportunities for decision. This book examines why the LSP'S provision of counsel to the poor resulted in litigation before the Supreme Court; why the justices were so responsive to the opportunities for decision presented by the poor in LSP cases; and how these opportunities for decision affected the course of our constitutional jurisprudence. During the writing of this book, I was fortunate to have many sources of support and I owe much to them all. J. Woodford Howard, Jr., and Francis E. Rourke at the Johns Hopkins University provided guidance and artfully mixed critiques with encouragement. Lawrence Baum, Milton Heumann, and Doris Marie Pro vine patiently read drafts, in whole or in part, and provided many thoughtful suggestions. John Kingdon helped stimulate my thoughts on explaining the Legal Services Program's success.